Le classi ceramiche della "tradizione mista" a Kos nel Tardo Bronzo IA - Vitale, Salvatore (Archaeologist) (Access archaeology., 2019)
This volume focuses on the pottery classes of the 'Entangled Tradition' recovered at the settlement of the 'Serraglio' on Kos during the early Late Bronze Age period. The results reveal new information on the chronology, typology, and decoration of Koan Painted Fine (PF) and Painted Medium-Coarse to Coarse (PMC-C) ceramics. Moreover, the analysis of manufacturing processes and consumption patterns contributes to a better comprehension of the socio-cultural and political context in which Koan entangled classes were produced. The data presented in this volume indicate that PF and PMC-C ceramics represent a unique case of fully entangled classes in the Aegean, which merge features of the Koan `Local Tradition' with characteristics of the Minoan potting tradition into a new technological and stylistic language. Contacts between these different cultures are explained based on the theoretical model provided by 'human mobility'. The specific Koan cultural synthesis was endorsed and promoted by the local elites of the 'Serraglio', who aimed to participate in the 'new environment' determined by the economic and cultural expansion of Neopalatial Crete. In this respect, the manufacture of Koan entangled classes served a dual role. On the one hand, using transport containers made in the PMC-C class, Koan products were exported and exchanged throughout the Aegean. In addition, the finer vessels of the Koan 'Entangled Tradition' were utilized for promoting Minoan-type social practices at the 'Serraglio'. Through these practices, Koan elites reshaped their identity and portrayed an image of higher status within the local social arena.